До питання виникнення та припинення прав на земельну ділянку для використання надр - Макаренко, О. Ю.; Макаренко, О. Ю.; Makarenko, О. (My University, 2012)
In the article the question of beginnings and cessation of the rights to the plot of land for use of bowels is investigated. There were picked out the main characteristics of beginnings and cessation of the rights to the plot of land for use of bowels, making for their special-purpose and integrity of object of using such natural resources as land and bowels.
Макаренко О. Ю. До питання виникнення та припинення прав на земельну ділянку для використання надр / О. Ю. Макаренко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 381-390.
Keywords: права на земельну ділянку для використання надр; виникнення та припинення прав на земельну ділянку для використання надр; цільове призначення та єдність мети використання земель; земельне право України; права на земельный участок для использования недр; возникновение и прекращение прав на земельный участок для использования недр; целевое назначение и единство цели использования недр; земельное право Украины; the right to land for the use of mineral resources; The origin and termination of land rights for the use of mineral resources; purpose and unity of purpose of use of mineral resources; Land Law of Ukraine